Qasim Avezov is the Head of the Culture Department (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article describes the approval of Kasim Avezov as the head of the Department of Arts of the KKASSR and the work he has done in the course of this activity. It was noted that he contributed to the development of the theater in the newly formed territories, attracted young people to it, in 1935-1936. in Karakalpak literature, the Poem made a great contribution to the formation of the genre.